Maldives Development Update, June 2020 : In Stormy Seas - World Bank (World Bank, Washington, DC, 2020)
Following three consecutive years of growth above 6 percent, the Maldivian economy kept momentum in 2019. Preliminary estimates indicate that real GDP decelerated slightly to 5.3 percent, from 6.9 percent in the previous year. Tourist arrivals reached a record high of 1.7 million, a 14.7 percent increase from 2018. Strong tourism growth compensated for softer construction activity, which grew by only 3.1 percent as many large infrastructure projects were completed in late 2018. This marked the slowest rate of construction growth since the public investment boom began in 2014. The global pandemic caused by the novel coronavirus (COVID-19) has impacted the Maldives’ economy more than any other country in South Asia. Although the Government acted quickly to protect lives, barring incoming travelers from affected areas as early as February 3 and closing its borders on March 27, a substantial domestic outbreak commenced on April 15. As this report is being written, nearly 2,000 people have tested positive for COVID-19 and 8 have lost their lives to the disease. The real toll of the pandemic, however, is much higher, with thousands of livelihoods affected by the shutdown of tourism. Tourist arrivals fell by 11.1 and 63.4 percent year-on-year (y-on-y) in February and March respectively and remained at zero for the entire second quarter. Cumulatively, the 65 percent y-on-y fall in tourist arrivals from February-May 2020 exceeds the decline in tourist arrivals experienced in the four months after the 2004 Indian Ocean tsunami. Construction has also been affected, as half the COVID-19 cases affect Bangladeshi nationals, many of whom work in the sector, and as external financing has dried up.